Psychometric properties of the vaccination fear scale (VFS-6) in Polish and their relationship with psychological distress - Malas, Olga; Załuski, Maciej; Makara-Studzińska, Marta (Frontiers in Psychiatry, 2025)
IntroductionPreventing vaccine hesitancy is an important effort by the clinician. The present study aimed to evaluate the factorial structure and psychometric properties of the Vaccination Fear Scale (VFS) in a Polish sample, as well as to examine its measurement invariance across sex and its associations with psychological distress.MethodsA sample of 455 adults from the general population, broadly representative of the general Polish adult population, (Mean age = 37.05, SD = 13.14; 72.3% female) was recruited. Participants completed the seven-item version of the VFS. A subsample of 153 individuals also completed the 21-items Depression, Anxiety, and Stress Scale (DASS-21). Confirmatory factor analyses (CFA) were conducted to compare unidimensional, two correlated factors, and second-order two-factor models for 7-items and 6-items versions.ResultsResults indicated that the 6-item version of the VFS (VFS-6), excluding item 5, provided superior fit compared to the 7-item version. The best-fitting model was a two-factor correlated structure (Cognitive factor: items 1, 2, and 4; Somatic factor: items 3, 6, and 7), confirming a clear cognitive-somatic structure. Measurement invariance analyses supported strict invariance between sexes. Internal consistency was high for both the total scale and its subfactors, and convergent and discriminant validity were satisfactory.ConclusionCorrelations with DASS-21 scores were low and non-significant, suggesting that vaccination fear is largely independent of general psychological distress measured as depression, anxiety and stress. These findings demonstrate that the VFS-6 is a reliable and valid instrument for assessing fear of vaccination in the Polish population. The results also clarify the role of item 5, and provide evidence for strict sex invariance, offering a robust tool for research and intervention planning.